The Influence of Empathy and Consumer Forgiveness on the Service Recovery Effect of Online Shopping - Wei, Jiahua; Wang, Zhenyu; Hou, Zhiping; Meng, Yongheng (Frontiers in Psychology, 2022)
The service failure of online shopping has always plagued online stores, but the current academic circles still lack to explore the service recovery of online shopping from the perspective of empathy and consumer forgiveness. Based on the service failure cases of real online shopping, this paper uses the method of situational experiment to carry out empirical research, discusses the impact mechanism of service recovery effect from the perspective of empathy and consumer forgiveness, and tests the moderating role of online store reputation.The results show that in the online shopping service recovery scenario, empathy has a positive impact on consumer forgiveness, consumer forgiveness has a positive impact on consumers repurchase intention, and consumer forgiveness plays a mediating effect between empathy and consumer repurchase intention; Online store reputation plays a moderating role in the relationship between consumer forgiveness and consumer repurchase intention. The research conclusion of this paper will help to expand the application of empathy and consumer forgiveness in the research of service recovery, enrich the theory of online shopping service recovery, improve the effect of online shopping service recovery, and promote the healthy development of online shopping business model.